PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP INITIAL PUBLIC OFFERING (IPO)UNDERPRICING DI INDONESIA - Purwanto .; Sri Wahyu Agustiningsih; Salman Faris Insani; Budi Wahyono (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2015)
This research trytoexaminewhethercorporate governancewhenthe company madean Initial Public Offering(IPO) affectthe level ofunderpricingshares of companies thatgo publicby usingthe period2002-2012.This studyfocuses onthe influence ofcorporate governance structureon the level ofunderpricingby usingcontrol variablesunderwriterreputation, return on assets (ROA), firm size, financial leverage, andreturn on equity(ROE). According tothe results ofprevious studies, these variablesgenerallytend toshowa significant effecton underpricingin companiesthatgo public This research is ekspost facto (causal comparative). Sample selection method used was purposive sampling and sample used was 131 sample companies doing anInitial Public Offering on the Indonesia Stock Exchange in the period 2002-2012. This study uses regression testing models. Regression analysis showed that onlytheunderwriterreputationsignificantly influenceunderpricing